PENGARUH PENAMBAHAN EKSTRAK JAHE (Zingiber Officinale) DAN ASAP CAIR (Liquid Smoke) DENGAN LAMA PENGASINAN TERHADAP KUALITAS KEDALAMAN RONGGA UDARA DAN LEMAK KUNING TELUR - Akbar, Andi; Abustam, Effendi; Hidayat, Muhammad Nur (Jurnal Ilmu dan Industri Peternakan, 2016)
ABSTRACT. This research was conducted in September s.d October 2013 . Housed in Laboratory Animal Products Technology, Faculty of Animal Husbandry, Hasanuddin University, Makassar. This study aimed to determine the effect of immersion time 10 % liquid smoke concentration and storage time on the quality of beef longissimus dorsi muscle bali (has outside). The research methodology is based on completely randomized design (CRD) with a general pattern that is 4 x 4 with 3 replications, Composition of treatment as follows: Factor I is a Long Soaking with A1 (0 minutes), A2 (30 minutes), A3 (60 minutes), A4 (90 minutes). Factor II is the long storage with B1 (0 weeks), B2 (1 weeks), B3 (2 weeks) and B4 (3 weeks). Data were analyzed by analysis of variance using a completely randomized design (CRD) consisting of 6 parameters of meat quality testing using the Least Significant Difference Test (BNT).Based on the results of various analysis and discussion, it can be concluded that the long soaking liquid smoke did not significantly affect the quality of meat while the storage time affects the quality of meat.